Answer:y = 65x/z
Explanation:
Suppose y varies directly with x and inversely with z. It means that as y increases or decreases, y increases or decreases while z decreases or increases respectively.
In order to remove the variation symbol and replace with an equation symbol, we would introduce a constant of variation, k. It becomes
y = kx/z
When x= 65 and z=5, then y= 26. We would substitute these value to get the constant of variation, k. It becomes
26 = 65k/5
65k = 65
k = 1
The equation of combined variation will be
y = 65x/z